“Exercise Is My Medicine”: A Qualitative Study Exploring the Experiences of Non-admitted Patients Receiving Physical Activity Promotion From Hospital Surgeons - Barrett, Stephen; Begg, Stephen; O'Halloran, Paul; Rodda, Kane; Barrett, Gabrielle; Kingsley, Michael (Frontiers in Public Health, 2022)
Background Hospital clinicians are increasingly encouraged to use outpatient consultations as an avenue to deliver opportunistic health promotion. There is a dearth of evidence regarding the acceptance of health promotion initiatives from hospital patients themselves. Methods We explored the experiences of non-admitted patients who, during a routine consultation with a hospital surgeon received a recommendation to increase physical activity (PA) and a recommendation to engage in a PA telephone coaching program. Twenty-two semi-structured interviews were conducted with individuals who had received the recommendation and proceeded to enroll in a telephone coaching intervention to identify factors that influenced behavior change. Data were analyzed thematically. Results Participants' age ranged between 42 and 66 years, with the average age being 54 years. Of the participants, 15 (68%) were women and 7 (32%) were men. Three major themes were identified: (1) the hospital visit represented an opportunity for behavior change that is not to be missed; (2) surgeons were influential in promoting PA change contemplation; and (3) patients welcomed a communication style that promoted autonomy. Conclusions Almost all patients considered receiving the recommendation to engage with the telephone coaching as acceptable and helpful toward PA change. Although working in time-restricted consultations, surgeons delivered the recommendation in a patient-centered, autonomy-supportive way, which influenced behavior change. Hospitals should explore avenues to integrate health promotion into routine care, confident of the acceptability and appropriateness of health promotion practice to hospital patients.